Decreased baroreflex sensitivity is linked to the atherogenic index, retrograde inflammation, and oxidative stress in subclinical hypothyroidism. (2nd January 2017) - Syamsunder, Avupati Naga; Pal, Pravati; Pal, Gopal Krushna; Kamalanathan, Chandrakasan Sadishkumar; Parija, Subhash Chandra; Nanda, Nivedita; Sirisha, Allampalli
ABSTRACT: Purpose/aim of the study : The present study investigated the link of hyperlipidemia, inflammation and oxidative stress (OS) to cardiovascular (CV) risks in subclinical hypothyroidism (SCH).Materials and methods : We enrolled 81 subclinical hypothyroid patients and 80 healthy subjects as control. Their CV and autonomic functions were assessed by spectral analysis of heart rate variability (HRV), continuous blood pressure variability (BPV) measurement and conventional autonomic function testing. Thyroid profile, lipid profile, immunological, inflammatory and OS markers were estimated and correlated with the baro-reflex sensitivity (BRS), the marker of sympathovagal imbalance (SVI) & CV risk.Results : Mean arterial pressure (MAP, P<0.0001), total peripheral resistance (TPR, P<0.0001), ratio of low-frequency to high-frequency power of HRV (LF-HF ratio) (P<0.0001) were significantly higher and BRS (P<0.0001) was significantly lower in SCH group than the control group. BRS significantly correlated with heart rate, MAP, LF-HF ratio, lipid risk factors, anti-thyroperoxidase antibody, thyroid-stimulating hormone, high-sensitive C-reactive protein (hsCRP), malondialdehyde (MDA) and SCH.Conclusions : It was concluded that SVI is associated with SCH. Though dyslipidemia, inflammation and OS contributed to decreased BRS, SCH per se contributed maximally to it. Decreased BRS could be a physiological basis of increased CV risks in patients with SCH.